Respon Guru dan Siswa SMA Terhadap Penggunaan Quipper School Dalam Blended Learning pada Pembelajaran Biologi - Abd. Muis, Abd. Muis; Bahri, Arsad (Biology Teaching and Learning, 2018)
Abstract. The effectiveness of a learning innovation cannot ignore the important aspects of student characteristics. The purpose of this study was to describe the response of high school teachers and students to blended learning (BL) using quipper school. Respondents of this study were 21 teachers and 81 students of class XI MIA 1 SMA Pangkajene Sidrap, Sidrap Regency. The response of teachers and students to the use of quipper school in blended learning in biology learning, measured by the teacher and student response questionnaire. The results showed that teachers and students gave a positive response to the use of quipper shool in BL. This proves that the use of quipper school in BL is effectively used in high school learning by considering various aspects such as student characteristics, availability of supporting facilities and infrastructure, and the ability of teachers to use technology. Keywords: blended learning, online learning, quipper school, teachers' response, students’ response.